Effect of canal preparation with TRUShape and Vortex rotary instruments on three‐dimensional geometry of oval root canals. (18th April 2017) - Arias, Ana; Paqué, Frank; Shyn, Stephanie; Murphy, Sarah; Peters, Ove A.
Abstract: The purpose of this study was to assess the geometry of non‐round root canals after preparation with TRUShape (a novel instrument with s‐shaped longitudinal design) in comparison to conventional rotary instrumentation using micro‐computed tomography. Twenty distal root canals of mandibular molars were randomly distributed in two groups to be shaped with either TRUShape or Vortex rotaries. Percentages of unprepared surface and volume of dentin removal for the entire canal and for the apical 4 mm were calculated. Canal transportation and the structure model index (SMI) were assessed. Data were compared with Student t‐tests. Shaping with both techniques resulted in similar prepared surface and volume of dentin removed, as well as the extent of canal transportation. The SMI shape factor was significantly lower for TRUShape preparations ( P = 0.04) suggesting less rounding during rotary preparation. Although both instruments were suitable for the preparation of oval canals, TRUShape appeared to better conform to the original ribbon‐shaped anatomy.